Pemanfaatan Sistem Telehealth Berbasis Web Pada Ibu Hamil : Kajian Literatur - Ezyla Purbaningsih; Tutik Sri Hariyanti (UIMA Press, 2020)
Introduction: Maternal mortality can occur as an indirect result of deteriorating clinical services. The distance to the Puskesmas and the limited time to check for pregnancy make telehealth services one of the solutions that can be taken. Objective: To identify several studies that have examined the use of telehealth in pregnant women. Methods: Literature review through the SPIDER search strategy, which is limited to 2015-2019. The databases used were: Scinapce, Science Direct, Elsevier, Starpage.com Results: 320,808 articles were identified that matched the search keywords, then focused on phenomena that were in accordance with the research objectives and six articles were analyzed. Telehealth is useful for classifying high-risk pregnancies, the use of telemedicine in gestational diabetes, care for high-risk pregnant women, maternal and child health care, care for pregnant women and in gestational diabetes. Conclusion: Telehealth is beneficial for pregnant women with regard to screening and prevention of risky pregnancies.